Associations between volatile fatty acid profiles, methane emissions, and rumen microbiota in sheep fed Ethiopian forage - Bekele, Wondimagegne; Mahawar, Lovely; Ramin, Mohammad; Simachew, Addis; Albrectsen, Benedicte Riber; Zegeye, Abiy (Frontiers in Microbiology, 2026)
This study was part of an in vivo investigation of methane (CH4) abatement feed on local Menz breed sheep in Ethiopia, conducted over 90 days period using a randomized complete block design. Sheep were subjected to four dietary treatments: Control, Acacia (Acacia nilotica), BSG (Brewer's Spent Grain), and Ziziphus (Ziziphus spina-christi). The aim of the study was to investigate the rumen microbial community composition, diversity, and their relationships with CH4 intensity. Rumen fluid was collected on days 0 (SD_0), 45 (SD_45), and 90 (SD_90), using an esophageal tube. The dynamics of the bacterial and archaeal domains were assessed by 16S rRNA gene sequencing. The sequencing results showed that 92.9% of ASVs were Bacteria, and 0.05% Archaea. At the genus level, Rikenellaceae RC9 gut group (18%), Prevotella (17%), and Candidatus Saccharimonas (8.9%) were the most abundant Bacteria, while Methanobrevibacter (88%) dominated the Archaeal genera across all treatment groups. Treatment feed significantly altered microbial profiles, notably reducing Methanobrevibacter abundance in CH4 abatement diets and increasing the presence of Methanosphaera. Shannon diversity increased in the abatement diet and decreased when the sheep were fed BSG. CH4 intensity was most strongly associated with the archaeal genus Methanomicrobium, but did not associate strongly with any other Bacteria or Archaea, although Methanobrevibacter and Methanosphaera were correlated negatively (r = –0.97). CH4 intensity also did not covary with volatile fatty acids (VFAs), of which Acacia yielded the highest acetate (772 mmol/mol) and BSG the highest propionate (172 mmol/mol) concentration. The volatile fatty acids (VFAs) showed a strong correlation: a positive correlation between acetate and butyrate (r = 0.80) and a strong negative correlation between acetate and propionate (r = –0.92). These findings highlight the complex relationship between diet, rumen microbiota, and fermentation products, with implications for CH4 mitigation strategies in sheep.